A STUDY OF NOVICE TEACHERS' CHALLENGES AT THEIR PRACTICAL TEACHING PHASE - Wagdi Rashad Ali Bin-Hady (INTERNATIONAL JOURNAL ON LANGUAGE, RESEARCH AND EDUCATION STUDIES, 2018)
Starting the teaching profession can be considered as challenging for novice teachers (Dickson et.al., 2014). Thus, this study aims to explore the linguistic difficulties that novice teachers encounter and the major defects that such teachers have in their lesson planning while demonstrating the lesson steps to their pupils. The sample of this study is nine of the fourth level students at the English department, college of education, Al-Mahra, Hadhramout university, for the academic year 2017-2018. The researcher uses qualitative research design. The data were collected using classroom observation and novice teachers' lesson plans. The study found that the majority of the Yemeni novice teachers have problems in pronunciations which if not amended will be transferred into the learners. Overuses of Arabic is also the second major problem that the novice teachers had. Moreover, time is not organized effectively during the lesson steps.   No enough activities are used in each lesson, and assessment is hardly done.  The study also revealed that the novice teachers have problems in preparing their lesson plans. Such problems start from the fogy teaching objectives and the warming up activities are minimized to just ask the class about the time and date of the day. Similarly, the activities are not enough to achieve the lesson objectives and finally the time of each lesson step is not set and assessment is not mentioned.